Effects of Selenomethionine on Cell Viability, Selenoprotein Expression and Antioxidant Function in Porcine Mammary Epithelial Cells - Chen, Jun; Zhang, Yinzhi; Lv, Yantao; Tian, Min; You, Jinming; Chen, Fang; Zhang, Shihai; Guan, Wutai (Frontiers in Nutrition, 2021)
This study investigated the effects of selenomethionine (Se-Met) on cell viability, selenoproteins expression and antioxidant function of porcine mammary epithelial cells (pMECs), to reveal the underlying molecular mechanism of Se-Met on the lactation performance and antioxidant capacity of sows in vitro. The pMECs were used as an in vitro model and were treated by various concentrations of Se-Met (0, 0.5, 1.0, 2.0, and 4.0 μM). Cells were analyzed for cell viability, selenoprotein transcriptome, selenoproteins protein expression, and antioxidant enzymes activities. The results showed that, with the increase of Se-Met concentrations, cell viability was increased firstly and then decreased at 24, 48, or 72 h post-treatment with maximum values at 0.5 μM Se-Met. As Se-Met concentrations increased, the mRNA expression of 17 selenoproteins was up-regulated firstly and then down-regulated with maximum values at 0.5 μM Se-Met. The 17 selenoproteins included SEPHS2, SELENOP, GPX1, GPX2, GPX3, GPX6, TXNRD1, SELENOK, SELENOW, DIO1, DIO2, DIO3, SELENOF, SELENOS, SELENOH, SELENOI, and SELENOT. Also, the protein expressions of SEPHS2, SELENOP, GPX1, and TXNRD1 and the glutathione peroxidase activity and thioredoxin reductase activity were highest at 0.5 μM Se-Met. In conclusion, 0.5 μM Se-Met promotes cell viability partially through improving selenoproteins expression and antioxidant function in porcine mammary epithelial cells, which supply a scientific nutritional regulation reference for improving mammary gland health in sows.